Kassinasma, a new generic replacement name for Kassinella Keller 1970 (Anthozoa: Streptelasmatida) non Borissiak 1956 (Brachiopoda: Strophomenacea) - Doweld, Alexander B. (Zootaxa, 2015)
The genus Kassinella was established by Keller (1960: 90) for extinct Lower Carboniferous (Tournaisian) corals from Kazakhstan. The name, however, is preoccupied by the senior homonym Kassinella Borissiak (1956: 50) (Brachiopoda), equally honouring N. G. Kassin, famous geologist and explorer of Kazakhstan.